2011
DOI: 10.1111/j.1540-8175.2011.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Endothelial Functions in Patients with Celiac Disease

Abstract: This research which aimed to evaluate endothelial dysfunction in patients with celiac disease is the first in the literature. As a result of this study, we found endothelial dysfunction at the macrovascular level in celiac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…We found no significant difference between antibody positive and antibody negative patients in terms of PWV and CIMT. Similar results were also observed in two different studies 20,21 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We found no significant difference between antibody positive and antibody negative patients in terms of PWV and CIMT. Similar results were also observed in two different studies 20,21 .…”
Section: Discussionsupporting
confidence: 79%
“…Although a link between CD and CVD remains weak, it is considered that chronic inflammatory condition in CD may be directly responsible for the development of endothelial dysfunction, leading to a subsequent increase in arterial stiffness and atherosclerotic lesions. A few studies in adults have suggested that CD is associated with premature atherosclerosis [19][20][21] . Endothelial dysfunction at the macrovascular level was found in adult celiac patients 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, because of giving early information about cardiac functions, TDE may be useful to obtain evidence of subclinical impairment of ventricular function. There are few published studies in the pediatric age group with Coeliac disease [31, 32]. Although our results showed a significant difference between the patient and control groups in terms of MV E′ and MV A′ among tissue Doppler echocardiographic parameters of left ventricle, no evidence of diastolic dysfunction was observed.…”
Section: Discussioncontrasting
confidence: 78%
“…In our previous study, we demonstrated macrovascular endothelial dysfunction in CD patients using a flow-mediated dilatation method [31]. This is the first study to investigate aortic function using echocardiography in CD patients, which revealed deteriorated aortic function.…”
Section: Discussionmentioning
confidence: 99%